2012
DOI: 10.1210/jc.2011-1855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestational Diabetes and Intrauterine Growth Restriction on the Offspring's Circulating Galanin at Birth

Abstract: Circulating galanin levels at birth are not affected by GDM and IUGR, providing no evidence for alternations in hypothalamic galanin expression and secretion in humans, as they were previously documented in experimental models. This fact precludes the use of plasma galanin as an early indicator for the development of obesity and metabolic syndrome in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
4
0
3
Order By: Relevance
“…Additionally, the sample size of the former study group (four men and seven women) limits the possibility to establish statistical correlations. In accordance with Legakis et al ., the present study shows a positive correlation with HOMA-IR and serum GAL levels17. Additionally, our study did not show significant differences in fasting glucose levels between obese and lean subjects, and neither showed any significant correlation between fasting glucose and serum GAL levels.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Additionally, the sample size of the former study group (four men and seven women) limits the possibility to establish statistical correlations. In accordance with Legakis et al ., the present study shows a positive correlation with HOMA-IR and serum GAL levels17. Additionally, our study did not show significant differences in fasting glucose levels between obese and lean subjects, and neither showed any significant correlation between fasting glucose and serum GAL levels.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, and contrary to our results, Legakis et al . showed that serum GAL levels increase significantly by 30 min in healthy individuals during OGTT, and return to baseline levels at 180 min17. Contrary to the group studied by Legakis et al .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This phenomenon may relate with complementary food supplements for infants more than 6–9 months old. In animal models, maternal hyperglycemia resulted in perinatal hyperglycemia and increased hypothalamic insulin levels, followed by findings of permanent dysplasia of hypothalamic nuclei regulating food intake and metabolism in the offspring [24]. These alterations may increase food intake, with preference for fat, and further increase the risk of overweight or obesity in offspring at adulthood [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, maternal hyperglycemia resulted in perinatal hyperglycemia and increased hypothalamic insulin levels, followed by findings of permanent dysplasia of hypothalamic nuclei regulating food intake and metabolism in the offspring [24]. These alterations may increase food intake, with preference for fat, and further increase the risk of overweight or obesity in offspring at adulthood [24, 25]. Thus, early infant diet on the growth and development of children who may be programmed for a faster growth trajectory may be decided by utero exposure to overnutrition from a diabetic pregnancy.…”
Section: Discussionmentioning
confidence: 99%